2016
DOI: 10.1158/1078-0432.ccr-15-2631
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TSC1, TSC2, and MTOR Are Associated with Response to Rapalogs in Patients with Metastatic Renal Cell Carcinoma

Abstract: Purpose We examined the hypothesis that mutations in mTOR pathway genes are associated with response to rapalogs in metastatic renal cell carcinoma (mRCC). Experimental Design We studied a cohort of mRCC patients who were treated with mTOR inhibitors with distinct clinical outcomes. Tumor DNA from 79 subjects was successfully analyzed for mutations using targeted next generation sequencing of 560 cancer genes. Responders were defined as those with partial response (PR) by RECIST v1.0 or stable disease with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 45 publications
6
153
0
Order By: Relevance
“…Interestingly, all of the mTOR-activating mutants direct mTORC1 activation through either complete TSC1 loss or mTOR-activating mutation was associated with long-term therapeutic benefit (30)(31)(32)(33). Furthermore, one recent study reported that mutations in mTOR, TSC1, or TSC2 were more common in responders than nonresponders; however, a substantial fraction of responders had no mutations in the mTOR pathway (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, all of the mTOR-activating mutants direct mTORC1 activation through either complete TSC1 loss or mTOR-activating mutation was associated with long-term therapeutic benefit (30)(31)(32)(33). Furthermore, one recent study reported that mutations in mTOR, TSC1, or TSC2 were more common in responders than nonresponders; however, a substantial fraction of responders had no mutations in the mTOR pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular mechanisms that underscore observed heterogeneous clinical benefits remain undetermined, and no predictive biomarkers are available to guide patient selection for therapy. Case studies of exceptional rapalog responders in kidney cancer, bladder cancer, and thyroid cancer demonstrated that loss-of-function mutations of tuberous sclerosis complex 1 (TSC1) and TSC2 or activating mutations of mTOR could be predictive for treatment response (30)(31)(32)(33)(34). On the other hand, a mutation in the FKBP-rapamycin-binding (FRB) domain of mTOR was reported to confer resistance to everolimus (33).…”
mentioning
confidence: 99%
“…For example, patients with metastatic disease and a mutation in mammalian target of rapamycin ( MTOR ) can show exceptional response to targeted agents such as everolimus [2931]. This finding is not unique to ccRCC and has been described in several other solid malignancies [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of patients' tissues revealed the expected predictive markers of response to the treatment. In a sample of 79 patients receiving mTOR, inhibitors sequencing showed that mutations in mTOR, TSC1 or TSC2 occurred more often in patients responding to therapy (Kwiatkowski et al 2016). In a clinical study comparing everolimus with sunitinib in clear cell RCC, it was found that mutations in the PBRM1 locus were related to longer survivability in patients receiving everolimus.…”
Section: Kidney Cancer Targeted Therapymentioning
confidence: 99%